2021
DOI: 10.3390/su13031131
|View full text |Cite
|
Sign up to set email alerts
|

Ghanaian SMEs Amidst the COVID-19 Pandemic: Evaluating the Influence of Entrepreneurial Orientation

Abstract: Entrepreneurial orientation has recently been touted as a tool for solving enterprise failures in emerged and emerging economies especially during and after an epidemic. This study aims at understanding the impact of entrepreneurial orientation on enterprise performance in the Ghanaian food processing industry by assessing the mediating effects of innovation types and intellectual property. Data were collected from 702 owners/managers in the food processing industry via survey questionnaires. The data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 123 publications
0
19
0
1
Order By: Relevance
“…The pandemic can only kindle innovation: organisations do not grow weaker searching for innovation to boost effectiveness and optimisation, often technology-based, but embark on the search for business model innovations with new energy to grow agile and resilient to the competitors [85,86], but most of all, to survive. The analyses demonstrated that innovation is the potion of survival [24][25][26][27][28]30,34], so modern business models should be based on them. Again, product, process, organisational, marketing [31][32][33] and management [34][35][36]87] innovations should be the primary focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic can only kindle innovation: organisations do not grow weaker searching for innovation to boost effectiveness and optimisation, often technology-based, but embark on the search for business model innovations with new energy to grow agile and resilient to the competitors [85,86], but most of all, to survive. The analyses demonstrated that innovation is the potion of survival [24][25][26][27][28]30,34], so modern business models should be based on them. Again, product, process, organisational, marketing [31][32][33] and management [34][35][36]87] innovations should be the primary focus.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated by the COVID-19 crisis, enterprises find new ways to survive and grow. This is particularly apparent in small and medium enterprises [24] that turned out to be susceptible to tremor and founded their survival strategies on entrepreneurship [25,26] and innovation [27,28]. Perceiving chaos as an opportunity [29], businesses employed creativity, innovation, and entrepreneurial spirit to solve problems and grasp opportunities in a changed environment [30].…”
Section: Business Reaction To the Covid-19 Crisismentioning
confidence: 99%
“…The consequences of the epidemic on firms are not generally limited to lowering pay, overtime without motivation to be more efficient, delay in emolument or otherwise, etc. Due to COVID-19 and the downswing of existing businesses and firms, many companies in developing and developed countries worldwide have an optimum effect [56,57]. A large number of employees lost their jobs, while others found their pay reduced.…”
Section: Literature Surveymentioning
confidence: 99%
“…In the Australian context, the role of entrepreneurial initiatives is as a catalyst to growth. A study in the Ghanaian SME food processing industry conducted by Li et al [76] reported that entrepreneurial orientation affects enterprise performance during the COVID-19 pandemic. Enterprise performance leads to the business survival of SMEs in the Ghanaian food processing industry.…”
Section: Discussion and Contributionsmentioning
confidence: 99%